2015
DOI: 10.1183/09031936.00009015
|View full text |Cite
|
Sign up to set email alerts
|

An official American Thoracic Society/European Respiratory Society statement: research questions in COPD

Abstract: Chronic obstructive pulmonary disease (COPD) is a leading cause of morbidity, mortality, and resource use worldwide. The goal of this official American Thoracic Society (ATS)/European Respiratory Society (ERS) research statement is to describe evidence related to diagnosis, assessment and management; identify gaps in knowledge; and make recommendations for future research. It is not intended to provide clinical practice recommendations on COPD diagnosis and management.Clinicians, researchers, and patient advoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
92
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(96 citation statements)
references
References 275 publications
(232 reference statements)
1
92
0
Order By: Relevance
“…Indeed, the coincidence of important research questions related to COPD between the document generated by the International Primary Care Respiratory Group (IPCRG) in 2010 [1] and the recently published American Thoracic Society (ATS)/European Respiratory Society (ERS) statement on research questions in COPD [2] is evidence of the agreement that exists among everyone interested in this topic.…”
Section: From the Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the coincidence of important research questions related to COPD between the document generated by the International Primary Care Respiratory Group (IPCRG) in 2010 [1] and the recently published American Thoracic Society (ATS)/European Respiratory Society (ERS) statement on research questions in COPD [2] is evidence of the agreement that exists among everyone interested in this topic.…”
Section: From the Authorsmentioning
confidence: 99%
“…In relation to the questions of how to implement guidelines and how to educate clinicians to tackle respiratory diseases, the ATS/ERS statement was neither a guideline, nor was it developed to teach clinicians how to tackle "respiratory diseases". The last two questions are very worthwhile goals that were not addressed by either the ATS/ERS statement [2] or the IPCRG document [1], and require a much wider audience to develop the appropriate framework for their research.…”
Section: From the Authorsmentioning
confidence: 99%
“…The recent European Respiratory Society/American Thoracic Society Task Force for COPD Research statement [1] requested new studies that "…evaluate the impact of age on the importance of identifying an airflow limitation (i.e. is it more important to identify asymptomatic airflow limitation in a 30-year-old than an 80-year-old?…”
Section: @Erspublicationsmentioning
confidence: 99%
“…KOLDITZ et al [10] analysed data from the German competence network for community acquired pneumonia (CAPNETZ) and found that mortality was up to 20% in patients with respiratory failure and increased further if the deterioration of the respiratory function starts later than 72 hours after hospital admission: demonstrating that treatment failure had been overlooked due to a lack of a standardised management plan for this patients. The COPD audit found that only 45.0% of the patients with mild and 77.2% with severe respiratory acidosis received mechanical ventilation, although the positive effect of this measure has been clearly demonstrated [11]. In addition, only 81.6% of patients with acute exacerbation of COPD underwent blood gas diagnostics at admission, although this has been strongly recommended in various guidelines.…”
mentioning
confidence: 99%
“…While this is available on coronary care or stroke units on the basis of a huge number of randomised controlled trials, the evidence in diagnostics and treatment of acute exacerbation of COPD is low. Most recommendations, with the exception of those for noninvasive ventilation, relating to acute exacerbation of COPD in the American Thoracic Society/ European Respiratory Society guidelines [11] remain vague and are not based on reliable study data. A lot of questions remain unanswered.…”
mentioning
confidence: 99%